Relationship Between Anxiety Levels and Delayed Breast Milk Let-Down in Postpartum Mothers at Prof. Dr. R.D Kandou General Hospital Manado - Noviani Polohoon; Sulistiyah Sulistiyah (Journal of Educational Innovation and Public Health, 2026)
Background: Anxiety in postpartum mothers is a psychological problem that can negatively impact maternal mental health, marital relationships, and the lactation process. This psychological disorder can inhibit the production and let-down of breast milk, which, if not addressed promptly, can lead to physical complications such as breast engorgement or mastitis, as well as hinder the fulfillment of the infant's nutritional needs. Objective: This study aimed to determine the relationship between anxiety levels and delayed breast milk let-down in postpartum mothers at Prof. Dr. R.D. Kandou General Hospital Manado. Methods: This research is an analytical survey with a cross-sectional design. The sample consisted of 30 postpartum mothers selected using non-probability sampling. Research instruments included questionnaires and interviews, with data analysis using the chi-square test. Results: The majority of respondents experienced moderate anxiety (60.0%) and had non-smooth breast milk let-down (53.3%). Statistical test results showed a p-value = 0.030, indicating a significant relationship between anxiety levels and delayed breast milk let-down. Conclusion: High anxiety levels in postpartum mothers contribute to delayed breast milk let-down. Psychological support for postpartum mothers is needed to maintain the smoothness of the breastfeeding process.